2013
DOI: 10.1002/ar.22674
|View full text |Cite
|
Sign up to set email alerts
|

A Stockpile of Ova in the Grass Frog Rana temporaria is Established Once for the Life Span. Do Ovaries in Amphibians and in Mammals Follow the Same Evolutionary Strategy?

Abstract: Most anuran amphibians produce high numbers of eggs during several consecutive breeding seasons. The question is still open whether oocytes are formed anew as a result of oogonial proliferation after each spawning or the definitive pool of oocytes is established during the juvenile period and is sufficient for the whole reproductive life span of a female. Our quantitative studies show that primary oogonia in adult female frogs can proliferate, but they fail to differentiate further and do not enter meiosis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The ovaries of amphibians are saccular structures, as in teleosts, but the germinal epithelium in amphibians is located at the periphery of the ovary, as in Ambystoma dumerilii (Uribe, 2009a), Rana temporaria (Ogielska et al, 2013), and Rana nigromaculata (Tanimura and Iwasawa, 1991), meanwhile in teleosts the germinal epithelium is located internally, surrounding the ovarian lumen. The previtellogenic ovaries of amphibian are thin; during the breeding season the ovaries grow to occupy much of the abdominal cavity and contain both previtellogenic and vitellogenic, yolked oocytes (Dodd, 1977;Lofts, 1984;Wallace and Selman, 1990;Uribe, 2009a,;Ogielska and Kotusz, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ovaries of amphibians are saccular structures, as in teleosts, but the germinal epithelium in amphibians is located at the periphery of the ovary, as in Ambystoma dumerilii (Uribe, 2009a), Rana temporaria (Ogielska et al, 2013), and Rana nigromaculata (Tanimura and Iwasawa, 1991), meanwhile in teleosts the germinal epithelium is located internally, surrounding the ovarian lumen. The previtellogenic ovaries of amphibian are thin; during the breeding season the ovaries grow to occupy much of the abdominal cavity and contain both previtellogenic and vitellogenic, yolked oocytes (Dodd, 1977;Lofts, 1984;Wallace and Selman, 1990;Uribe, 2009a,;Ogielska and Kotusz, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The germinal epithelium of the common frog Rana temporaria presents yet another variation on the theme: oogonia in the adult may proliferate but fail to enter meiosis, and there is no regeneration of new follicles after a spawning season. This anuran has functional lifetime determinate reproduction as represented by the pool of follicles established in the juvenile (Ogielska et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the somatic context of the gonad determines the destination of the germinal cells (Evans et al, 1977). In anuran amphibians, a subpopulation of oogonia begins meiosis on every reproductive cycle, maintaining a niche of oogonia that serve as a reserve for the subsequent reproductive cycles (Bukovsky et al, 2005; Witschi, 1929); nevertheless, it has been reported at least an exception on R. temporaria , where a reservoir of oocytes establish in a single event (Ogielska et al, 2013). With the beginning of the meiosis, the ovarian morphology modifies due to the ovary grows because of the formation of the ovarian cavity and the thickening of the cortex, where some oogonia located at this ovarian cortex start meiosis increasing the number of oocytes at the diplotene stage in this region (Figure 2f) (Goldberg, 2015; Uribe, 2011).…”
Section: Germline Differentiation (Initiation Of Meiosis)mentioning
confidence: 99%
“…The situation is different in females where meiosis starts early, so in developing ovaries we can observe both mitotically dividing gonocytes and meiocytes up to early diplotene that form a limited stockpile for the entire female’s life (for details see Ogielska et al . 60 ). Meiocytes (but not gonocytes) in amphibians form isogenic groups and are encapsulated inside cysts; only in females diplotene oocytes are individual cells (each inside its own ovarian follicle).…”
Section: Introductionmentioning
confidence: 99%